Bevacizumab for Hearing Preservation in Neurofibromatosis Type 2: Emphasis on Patient-Reported Outcomes and Toxicities. (March 2019) - Sverak, Pavlina; Adams, Meredith E.; Haines, Stephen J.; Levine, Samuel C.; Nascene, David; Sommer, Katherine; Dusenbery, Kathryn; Huang, Tina C.; Moertel, Christopher
Objective: Bevacizumab for hearing preservation in patients with neurofibromatosis type 2 (NF2) is an emerging practice. We set out to characterize the effectiveness and toxicity of bevacizumab in our patient group. Study Design: Case series with chart review. Setting: Tertiary referral center. Subjects and Methods: Seventeen consecutive patients with NF2 received bevacizumab treatment for vestibular schwannomas, including 2 patients treated to maintain cochlear implant performance. Volumetric analysis of serial magnetic resonance imaging scans was used to evaluate radiographic response, and hearing response was evaluated with serial audiograms. Patient-reported outcomes were also assessed, including subjective hearing improvement, changes in tinnitus, vertigo, headaches, ear pain, and improvement in ability to communicate via telephone. Results: A positive radiographic response occurred in 8 of 17 (47%) patients and the median tumor volume change was a tumor decrease of 19%. A positive hearing response was recorded in 5 of 9 (56%) patients. Two patients had a word recognition score improvement over 40%. There was an approximately 40% improvement in patient-reported outcomes. Primary toxicities included hypertension, proteinuria, dysgeusia, and amenorrhea. Conclusion: Bevacizumab treatment was followed by hearing improvement in 56% of patients, while decreased tumor volume was noted in 47%. These outcomes agree favorably with prior reported series. There were significant improvements in patient-reported outcomes that have not been described previously.